2020
DOI: 10.3389/fcell.2020.00348
|View full text |Cite
|
Sign up to set email alerts
|

HOTTIP Predicts Poor Survival in Gastric Cancer Patients and Contributes to Cisplatin Resistance by Sponging miR-216a-5p

Abstract: Gastric cancer (GC) is a significant public health burden worldwide, and cisplatin resistance is the leading cause for the failure of chemotherapy in this disease. Previous studies have revealed that HOXA transcript at the distal tip (HOTTIP) is involved in the pathology of GC and is associated with poor overall survival. However, the functional role of HOTTIP in GC chemoresistance remains unclear. In this study, quantitative real-time PCR was used to analyze HOTTIP expression in GC cell lines and in tissues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…The process of autophagy in particular in GC is ancient, regulating cellular mechanisms and homeostasis [21] .Several researches have demonstrated that this process is related to some proteomics and chemotherapeutic resistance in GC victims [22,23] . Studies have found that the autophagy of gastric cancer cells with enhanced chemotherapy-drug resistanceisenhanced, and inhibition of autophagy can eliminate chemotherapy-resistance [24,25] .Considering the importance of autophagy in chemotherapy resistance of GC, we can further explore the prognostic value of autophagy in the treatment of GC. In this study, we combined TCGA and GEO databases to accomplish our work.…”
Section: Discussionmentioning
confidence: 98%
“…The process of autophagy in particular in GC is ancient, regulating cellular mechanisms and homeostasis [21] .Several researches have demonstrated that this process is related to some proteomics and chemotherapeutic resistance in GC victims [22,23] . Studies have found that the autophagy of gastric cancer cells with enhanced chemotherapy-drug resistanceisenhanced, and inhibition of autophagy can eliminate chemotherapy-resistance [24,25] .Considering the importance of autophagy in chemotherapy resistance of GC, we can further explore the prognostic value of autophagy in the treatment of GC. In this study, we combined TCGA and GEO databases to accomplish our work.…”
Section: Discussionmentioning
confidence: 98%
“…Several researches demonstrated this process is related to some proteomics and chemotherapeutic resistance in GC victims [22,23] . Studies have found that gastric cancer cells with enhanced resistance to chemotherapy have enhanced autophagy, and inhibition of autophagy can eliminate chemotherapy-resistance [24,25] . Considering the importance of autophagy in chemotherapy resistance of GC, we can further explore the prognostic value of autophagy in the treatment of GC.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been found to regulate autophagy and drug resistance ( Figure 5B) by acting as a competing endogenous RNA (ceRNA) or directly binding to proteins to modulate their expression and functions (as summarized in Table 2). It has been found that the expression levels of HOTTIP (HOXA distal transcript antisense RNA), MALAT1 (metastasis associated lung adenocarcinoma transcript 1), and HULC (hepatocellular carcinoma up-regulated long non-coding RNA) are elevated in chemotherapy-resistant gastric cancer cell lines and tumor tissues (YiRen et al, 2017;Xin et al, 2019;Zhao et al, 2020). Zhao et al (2020) have indicated that HOTTIP may function as a ceRNA of miR-216a-5p, increasing the expression level of BCL-2 and decreasing the expression level of Beclin-1.…”
Section: Regulatory Effects Of Lncrnas On Autophagy-mediated Gastric mentioning
confidence: 99%
“…It has been found that the expression levels of HOTTIP (HOXA distal transcript antisense RNA), MALAT1 (metastasis associated lung adenocarcinoma transcript 1), and HULC (hepatocellular carcinoma up-regulated long non-coding RNA) are elevated in chemotherapy-resistant gastric cancer cell lines and tumor tissues ( YiRen et al, 2017 ; Xin et al, 2019 ; Zhao et al, 2020 ). Zhao et al (2020) have indicated that HOTTIP may function as a ceRNA of miR-216a-5p, increasing the expression level of BCL-2 and decreasing the expression level of Beclin-1. Further studies have shown that HOTTIP overexpression inhibits autophagy and induces DDP resistance in gastric cancer while the silencing of HOTTIP increases the sensitivity of gastric cancer cells to DDP ( Zhao et al, 2020 ).…”
Section: Dual Roles Of Autophagy In Chemoresistance Of Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation